2014
DOI: 10.1130/g35818.1
|View full text |Cite
|
Sign up to set email alerts
|

Climatic control of the late Quaternary turbidite sedimentology of Lake Kivu, East Africa: Implications for deep mixing and geologic hazards

Abstract: The Lake Kivu catchment in the East African Rift is subject to various geologic hazards, including frequent volcanic eruptions, earthquakes, and potential limnic overturns and degassing events. Integration of high-resolution seismic reflection data, 14 C dated sediment cores, and lake-floor bathymetry reveals large axial and transverse turbidite systems in the eastern basin of the lake. The turbidites were sourced by hyperpycnal river flows during exceptional floods, and the temporal occurrence of the turbidit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 24 publications
2
43
0
Order By: Relevance
“…Haberyan and Hecky (11) reported coarse material, including cobble sized, in deep water cores and suggested water levels may have fallen in the late Pleistocene as much as 300 m below the modern level. Similarly, Zhang et al (6) concluded, from a suite of more recently obtained cores, that water levels fell at least 380 m below the modern level 12,700 cal y BP, which would have placed the water level below our K19 coring site (Fig. 1).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Haberyan and Hecky (11) reported coarse material, including cobble sized, in deep water cores and suggested water levels may have fallen in the late Pleistocene as much as 300 m below the modern level. Similarly, Zhang et al (6) concluded, from a suite of more recently obtained cores, that water levels fell at least 380 m below the modern level 12,700 cal y BP, which would have placed the water level below our K19 coring site (Fig. 1).…”
Section: Discussionsupporting
confidence: 60%
“…S1). We also used a younger date of 2,172 ± 95 cal y BP in another piston core from Lake Kivu (K13-20A), which Zhang et al (6) correlated stratigraphically to ∼15 cm above the base of the lower carbonate interval in core 19A, i.e., at ∼313 cm blf. We used these dates to construct an age model for this core ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5) suggests deep-water mixing and upwelling of nutrient-rich waters to enhance algal productivity (Zhang et al, 2014). As with the AD 600 event, violent waves would have resulted from this large subaquatic slide; the waves are the likeliest explanation for reworked sand deposits (RDL1) at core PAV09-C5 site.…”
Section: Ad 1300 Slope Failure (Se2)mentioning
confidence: 92%
“…Lake Kivu has experienced drastic water-level fluctuations in the late Pleistocene (Zhang et al, 2014;Wood et al, 2015). The most recent lowstand occurred at~12.2 ka, during which lake-levels were~380 m below present, indicated by paleodeltas on seismic reflection profiles and sediment cores that reveal shallow-water ooids overlying deltaic sands (Zhang et al, 2014). This pronounced lowstand is also evidenced by drowned drainage systems (Fig.…”
Section: Lake Kivumentioning
confidence: 96%
“…Today, Lake Kivu discharges south to Lake Tanganyika via the Ruzizi River, and is the major contributor to the salt budget of Lake Tanganyika (Stoffers and Hecky, 1978). Lake Kivu has experienced drastic water-level fluctuations in the late Pleistocene (Zhang et al, 2014;Wood et al, 2015). The most recent lowstand occurred at~12.2 ka, during which lake-levels were~380 m below present, indicated by paleodeltas on seismic reflection profiles and sediment cores that reveal shallow-water ooids overlying deltaic sands (Zhang et al, 2014).…”
Section: Lake Kivumentioning
confidence: 99%